2019
DOI: 10.18196/agr.5280
|View full text |Cite
|
Sign up to set email alerts
|

The Conversion of Agricultural Land in Urban Areas (Case Study of Pekalongan City, Central Java)

Abstract: Agricultural land in urban areas has a strategic role as a provider of food for city resident, as well as supporting the environment of the urban area. The important role of the existence of agricultural land in urban areas over the past few decades faces a serious threat, namely the occurrence of agricultural land conversion.Therefore, this research was carried out with the aim to analyze the trend of agricultural land conversion in urban areas and to find out the factors that influence the agricultural land … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The increase in the area of planting shallots should be managed efficiently to increase productivity and minimize the conversion of agricultural land [28]. Thus, land expansion efforts can be carried out because the land is still available.…”
Section: Allocative Efficiency Of Shallot Farmingmentioning
confidence: 99%
“…The increase in the area of planting shallots should be managed efficiently to increase productivity and minimize the conversion of agricultural land [28]. Thus, land expansion efforts can be carried out because the land is still available.…”
Section: Allocative Efficiency Of Shallot Farmingmentioning
confidence: 99%
“…In Indonesia, agricultural land is frequently converted to non-agricultural land quite often occurs in several areas, especially in urban and suburban areas. In Pekalongan City, the conversion of agricultural land to non-agricultural land increased by 1.26% per year on average from 1989 to 2017 [5]. In addition, a study in the Special Region of Yogyakarta found that the agricultural land decreased by 0.48% every year [6].…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted in the Special Region of Yogyakarta showed that the sustainability of agricultural land could be influenced by social factors, including the interest of the younger generation to participate in the agricultural sector [14]. Furthermore, the level of farmers' welfare is also a determining factor for the sustainability of agricultural land [5]. Research in Pekalongan City even shows that the sustainability of agricultural land will depend on environmental conditions, including irrigation channel conditions and irrigation water quality [15].…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural land, especially in Java, is shrinking from year to year. The growth of urban areas has caused agricultural land to be converted into non-agricultural land, especially for housing [3,4]. The creation of new area of agricultural land is relatively slower than the loss of agricultural land for other uses.…”
Section: Introductionmentioning
confidence: 99%